Towards enterprise resource planning system implementation in UiTM / Fatimah Kamali@Ali - Kamali@Ali, Fatimah (2005)
Enterprise Resource Planning (ERP) system become famous in most industries all over the world. Recently, education sector slowly moved to ERP systems. ERP system is difficult and costly to implement. Studies show that the task to implement ERP system is not easy. It needs a lot of investment no matter in term of tangible or intangible material. ERP system has many advantages and many people believe it also can give a lot of benefits to education industry. For that reason, this research will investigate how ERP system can fit with the education industry. This research also highlight on Uitm current system performance. The research approaches for this research are project planning, data collection and data analysis/findings. Information is collected by interview, emails, case study review and questionnaire distributions. From the findings, there are many application systems used in Uitm. The integration concepts of ERP systems can cormected different applications and standardize Uitm's administration.